The influence of training, gender, and work experience on the performance of air traffic controller personnel - Hutabarat, Liber Tommy; Pasa, Inda Tri; Saragih, Nisa Azhari; Pramono, Agung; Sony, Morits (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Limited studies have examined the combined impact of training, gender, and work experience on air traffic controllers' (ATC) performance. This study examines the simultaneous influence of training, gender, and work experience on ATC performance at AirNav Indonesia’s Medan Branch, aiming to identify dominant predictors and policy implications. A quantitative associative design was employed with saturated sampling of 69 ATC personnel holding Aerodrome Controller Ratings. Data were collected via validated questionnaires (Cronbach’s α > 0.7) and standardized rating tests, then analyzed using multiple regression (α = 0.05). The model explained 26% of performance variance (R² = 0.26, F(3,56) = 6.572, p = 0.001). Training (β = 0.344, p = 0.010) and work experience (β = 0.286, p = 0.031) were significant, while gender (β = -0.078, p = 0.529) was insignificant. The data analysis results indicate that the simultaneous F test result's significance value is sig 0.001 <0.05, which means they have a simultaneous effect. The findings emphasize prioritizing recurrent training programs and experience-based assignments for ATC. The remaining 74% unexplained variance, particularly the minimal explained variance in the current model, highlights the need for future research to explore additional performance factors such as cognitive abilities and team dynamics, while the findings continue to support gender-neutral scheduling policies.